1992
DOI: 10.1093/ajcn/55.3.645
|View full text |Cite
|
Sign up to set email alerts
|

The role of breakfast In the treatment of obesity: a randomized clinical trial

Abstract: Fifty-two moderately obese adult women were stratified according to their baseline breakfast-eating habits and randomly assigned a weight-loss program. The no-breakfast group ate two meals per day and the breakfast group ate three meals per day. The energy content of the two weight-loss programs was identical. After the 12-wk treatment, baseline breakfast eaters lost 8.9 kg in the no-breakfast treatment and 6.2 kg in the breakfast treatment. Baseline breakfast skippers lost 7.7 kg in the breakfast treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(181 citation statements)
references
References 14 publications
8
166
0
3
Order By: Relevance
“…4 Hourly distribution of energy intake per 24 h during the breakfast ( ) and no-breakfast ( ) conditions for male participants who typically eat breakfast at least 5 times/week typically observed in experimental situations compared with free-living surveys (36) , this psychological difference between male and female participants could account for the different responses between the female highfrequency breakfast eaters and the male participants. Differences between the female high-and low-frequency breakfast eaters may be linked to differences in routinedriven eating habits and/or to dietary restraint between regular and irregular breakfast eaters (27,41) .…”
Section: Discussionmentioning
confidence: 99%
“…4 Hourly distribution of energy intake per 24 h during the breakfast ( ) and no-breakfast ( ) conditions for male participants who typically eat breakfast at least 5 times/week typically observed in experimental situations compared with free-living surveys (36) , this psychological difference between male and female participants could account for the different responses between the female highfrequency breakfast eaters and the male participants. Differences between the female high-and low-frequency breakfast eaters may be linked to differences in routinedriven eating habits and/or to dietary restraint between regular and irregular breakfast eaters (27,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Some suggest that skipping breakfast results in a decrease in the total daily intake of energy [27], but others have shown that it may instead lead to increased calorie consumption [28]. There is also evidence showing that lower food consumption at breakfast may accompany higher intakes at lunch and dinner [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, meal skipping, especially breakfast skipping, is associated with overeating later in the day, due to intense hunger followed by ingestion of high-fat, sugar-dense snacks (11) .…”
mentioning
confidence: 99%